Role of Sex and Early Life Stress Experience on Porcine Cardiac and Brain Tissue Expression of the Oxytocin and H2S Systems - Franziska Münz; Nadja Abele; Fabian Zink; Eva-Maria Wolfschmitt; Melanie Hogg; Claus Barck; Josef Anetzberger; Andrea Hoffmann; Michael Gröger; Enrico Calzia; Christiane Waller; Peter Radermacher; et al. (Biomolecules)
Early life stress (ELS) significantly increases the risk of chronic cardiovascular diseases and may cause neuroinflammation. This post hoc study, based on the material available from a previous study showing elevated “serum brain injury markers” in male control animals, examines the effect of sex and/or ELS on the cerebral and cardiac expression of the H2S and oxytocin systems. Following approval by the Regional Council of Tübingen, a randomized controlled study was conducted on 12 sexually mature, uncastrated German Large White swine of both sexes. The control animals were separated from their mothers at 28–35 days, while the ELS group was separated at day 21. At 20–24 weeks, animals underwent anesthesia, ventilation, and surgical instrumentation. An immunohistochemical analysis of oxytocin, its receptor, and the H2S-producing enzymes cystathionine-β-synthase and cystathionine-γ-lyase was performed on hypothalamic, prefrontal cortex, and myocardial tissue samples. Data are expressed as the % of positive tissue staining, and differences between groups were tested using a two-way ANOVA. The results showed no significant differences in the oxytocin and H2S systems between groups; however, sex influenced the oxytocin system, and ELS affected the oxytocin and H2S systems in a sex-specific manner. No immunohistochemical correlate to the elevated “serum brain injury markers” in male controls was identified.